REVERSIBILITY OF COMPLETE HEART BLOCK AFTER ACUTE ANTERIOR WALL MI - KHAN , MA; PERVEZ , N; REHMAN , FU; KHAN , AG; HASHIM , M; BARI , SA; QADEER , A; KAKAR , SU (Biological and Clinical Sciences Research Journal, 2024)
Acute myocardial infarction (MI) can result in varying degrees of heart block, most commonly in inferior wall MI. Identifying the reversibility of complete heart block (CHB) is crucial for guiding clinical management, particularly in determining the need for temporary or permanent pacemaker implantation. Objective: To determine the frequency of reversibility of complete heart block in patients presenting with acute myocardial infarction at Bolan Medical Complex, Quetta. Methods: This cross-sectional study was conducted at Bolan Medical Complex, Quetta, from March 2022 to June 2023. A total of 100 patients aged 18–65 years presenting with syncope and atypical chest pain were included. All patients underwent coronary angiography to identify ischemic causes of bradyarrhythmias. Temporary pacemaker dependency was monitored for two weeks, and permanent pacemaker implantation was performed if necessary. Data on demographic and clinical characteristics were collected and analyzed using SPSS version 22.0. Descriptive statistics were calculated, and the association between heart block reversibility and clinical variables was assessed using the Chi-square test, with p ≤ 0.05 considered significant. Results: The mean age of the patients was 52.5 ± 14.8 years, with 60% male and 40% female patients. The prevalence of diabetes, hypertension, and smoking was 40%, 55%, and 43%, respectively. CHB occurred in 7% of patients aged 16-35 years and 8% in those aged 36-65 years. The overall reversibility rate of CHB was 48%. A statistically significant association (p < 0.05) was found between second-degree atrioventricular (AV) block and CHB in relation to reversibility. Conclusion: Complete heart block in patients with acute myocardial infarction is often reversible, particularly in those with mild coronary artery disease. Temporary pacemaker use should be considered before deciding on permanent pacemaker implantation to allow time for potential spontaneous recovery.